THE INFLUENCE OF LIGHT STABILIZERS AND NANOSIZED PARTICLES OF SILICA ON THE RATE OF DESTRUCTION OF POLYMER COATINGS UNDER THE UV RADIATION - БІЛОУСОВА, А. О. (Technologies and Engineering, 2023)
Purpose. Research of the influence of adding nanosized additives and ultraviolet stabilizers to thin-layer coatings on their destruction under the action of ultraviolet radiation. Methodology. In the work, a styrene-acrylic copolymer was used as a polymeric binder. A light stabilizer of basic hindered amine (HALS) was used as a UV absorber. Silica was used as a filler and UV blocking agent. The coating was applied to polished 6063 aluminum substrates and KBr glass by pneumatic spraying. The chemical transformations in the coating composition were studied using infrared spectrometry. The carbonyl index was used to characterize the degree of polymer degradation. The characterization of chemical transformations on the surface was carried out by measuring the wetting angle Findings. The work shows that nanosized particles at a content of 30 wt. % accelerate the oxidation of the base polymer. At the same time, the content of nanoparticles of 30–50 wt. % slows down the loss of mass and thickness of the coating on the substrate by 2,5–3 times. It has been shown that films based on pure styrene-butyl methacrylate with an initial water wetting angle of 88° during an hour of exposure significantly increase hydrophilicity: the wetting angle decreases to 40°. Originality. As a result of the work, the degree of influence of silica nanoparticles on the physical and chemical properties of the coating in the system film-forming agent – inorganic filler with the addition of a UV stabilizer was determined. Practical value. The revealed regularities showed that nanosized silica particles affect the photodegradation of thin-layer coatings based on styrene-butyl methacrylate film-forming agent. From the point of view of ensuring the stability of water repellency for systems intended for use in atmospheric conditions, this effect is negative. The issue of increasing stability requires further research.